Environmental transfers against global warming: a credit-based program. (30th March 2006) - Matsueda, Norimichi; Futagami, Koichi; Shibata, Akihisa
This paper investigates the impacts of institutionalising a credit-based transfer program between developing and developed countries. Such a program is expected to become an essence of the Clean Development Mechanism in the Kyoto protocol. The provisions of financial and technological transfers are incorporated simultaneously into a dynamic game model of global stock pollution, where the efficiency in emission abatement is also described as a stock variable. Our numerical simulation indicates that a credit-based transfer program can be more beneficial for a recipient country as well as for a donor country, than a non-credit-based transfer program.